Disc Battery-The escalating risk of ingestion by children in IraqAnd subsequent clinical events and complications. - Jabir, Sabah , N.; Al-Assal, Muthana D. ,; Mohammed, Ahmed . , A (AL-Kindy College Medical Journal, 2013)
Background: Disc battery ingestion is a commonserious problem in Iraq. It increase in the last yearsbecause of the increase in number of electronic toysthat uses these batteries. These batteries containsmany types of irritant chemicals that increases therisk of it's ingestion.Methods:We reviewed the medical records ofchildren aged between 1year and 7 yearsold admitted to Surgical Specialty Hospital/BaghdadMedical City due to disc battery ingestion fromJanuary 2007 through December 2010). The diagnosisof disc battery ingestion was based upon history,clinical symptoms, and results of imaging studies.The clinical data reviewed included sex, age, clinicalmanifestation and duration of symptoms, hospitalcourse, imaging findings, and endoscopic results.Results: 50 patients were admitted to Thoracic andvascular Department/Surgical SpecialityHospital/Baghdad Medical city Complex (26 malesand 24 females) of disc battery ingestion with a meanage of 1.873 years (range, 7 months to 7 years).Fourty one patients had Symptoms of Dysphagia,vomiting, nausea, and abdominal pain. Four caseswith no history of disc battery ingestion and wereaccidentally found by X ray studies. Two patientscomplained from Aspiration and chalking, twopatients had mediastinitis and died at later on due tosepsis, and only one case had surgical emphysema.Thirty-eight cases had their batteries impacted in theupper esophagus and Nine cases had their batteriesimpacted in mid-esophagus, and Three cases had theirbattery impacted in the lower-